Perancangan Platform UMNA untuk Pelaksanaan Umrah Mandiri dengan Pendekatan Human-Centered Design - Johara Johara; Osly Usman; Ryna Parlyna (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The growing public interest in independent Umrah in Indonesia has not been matched by adequate digital infrastructure for novice users, resulting in procedural confusion, fear of visa rejection, cost uncertainty, and limited visibility of post-transaction travel status. This study designs the UMNA Platform, a digital solution that integrates the entire independent Umrah planning process through step-by-step navigation, dynamic cost calculation, visa administration support, and a centralized user control center. Employing a Human-Centered Design approach through five Design Thinking stages within a Waterfall SDLC framework, the research covers requirement analysis, system design, implementation, testing, and finalization. The unit of analysis comprises prospective urban Muslim pilgrims aged 20–45 in the Jabodetabek area. Data were analyzed qualitatively, through social media observation and pre-research questionnaires to identify user pain points, and quantitatively, using Black-Box Testing for functional validation and the System Usability Scale (SUS) for usability measurement. All twenty functional test scenarios achieved a 100% Pass status, and all four usability tasks reached a 100% completion rate, with an average SUS score of 82.75, exceeding the acceptability threshold. Integrating cost transparency, guided navigation, and travel status visibility was shown to enhance user confidence and ease of use. The UMNA Platform is expected to reduce consumer confusion and strengthen pilgrims' autonomy in performing Umrah independently.